Occurrence of Drug Resistant Candida Species in the Sputum of TB Clinic Attendees in and Around Chidambaram, Tamilnadu, India - V. Udhaya, K.K. Prasobh and (Journal of Experimental Sciences, 2010)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> ABSTRACT: Three years constant study was performed in order to screen the drug resistant Candida presence in the sputum of TB clinic attendees in and around Chidambaram, Tamilnadu, India. Totally 3100 sputum specimens were screened by using the routine mycological procedures. We could able to obtain 20.5% of Candida strains from 3100 TB clinic attendees and Candida albicans, Candida tropicalis, Candida dubliniensis and Candida krusei was identified. Overall based on our study report we could able to report 48%, 25% and 22% antifungal resistance by Candida strains towards the antifungal drugs Nystatin, Azole drugs and Amphotericin B. From this we can conclude and suggest that the occurrence of drug resistant Candida strains in the sputum/ respiratory tract of the patients with respiratory tract infections is not uncommon. Therefore the periodical survey of the drug resistant Candida strains is essential not only to for the development of new antifungal drugs and in the appropriate antifungal drug selection for the earliest treatment for the patient care, but also equally important for the prevention of these drug resistant Candida transmitted from the patients to the public. Â Key words: Candida, Drug resistance — Department of Medical Microbiology, Rajah Muthiah Medical College & Hospital, Annamalai University, Chidambaram, Tamilnadu, India — Please Cite This Article As: K.K. Prasobh and V. Udhaya. 2010. Occurrence of Drug Resistant Candida Species in the Sputum of TB Clinic Attendees in and Around Chidambaram, Tamilnadu, India. J. Exp. Sci. 1(4):43-47. Â